2014
DOI: 10.4315/0362-028x.jfp-14-106
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Tolerance of O157 and non-O157 Shiga Toxigenic Strains of Escherichia coli, Salmonella, and Potential Pathogen Surrogates, in Frankfurter Batter and Ground Beef of Varying Fat Levels

Abstract: The non-O157 Shiga toxigenic Escherichia coli (STEC) serogroups most commonly associated with illness are O26, O45, O103, O111, O121, and O145. We compared the thermal tolerance (D55°C) of three or more strains of each of these six non-O157 STEC serogroups with five strains of O157:H7 STEC in 7% fat ground beef. D55°C was also determined for at least one heat-tolerant STEC strain per serogroup in 15 and 27% fat ground beef. D55°C of single-pathogen cocktails of O157 and non-O157 STEC, Salmonella, and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…An increased fat content in food products increased the heat resistance of E. coli in some studies (Line et al, 1991; Huang et al, 1992; Ahmed et al, 1995; Smith et al, 2001; Liu et al, 2015), while other studies reported decreased resistance, no effect, or strain-specific effects (Kotrola and Conner, 1997; Vasan et al, 2014; Liu et al, 2015). The potential direct effects of fat on heat resistance of E. coli are confounded by the strong effect of fat on heat transfer in solid foods.…”
Section: Effects Of Salt or Sugar Addition In High Moisture Foodsmentioning
confidence: 97%
“…An increased fat content in food products increased the heat resistance of E. coli in some studies (Line et al, 1991; Huang et al, 1992; Ahmed et al, 1995; Smith et al, 2001; Liu et al, 2015), while other studies reported decreased resistance, no effect, or strain-specific effects (Kotrola and Conner, 1997; Vasan et al, 2014; Liu et al, 2015). The potential direct effects of fat on heat resistance of E. coli are confounded by the strong effect of fat on heat transfer in solid foods.…”
Section: Effects Of Salt or Sugar Addition In High Moisture Foodsmentioning
confidence: 97%
“…When ground beef fat content increased from 7 to 30% and patties were frozen, then thawed or refrigerated before cooking on a gas grill, there was a greater inactivation of E. coli O157:H7. Additionally, thermal processing steps used to eliminate E. coli O157:H7 can also be utilized to eliminate non-O157 STEC, only a few strains may posses a higher thermal tolerance and need a different type of processing (Vasan et al, 2014). Furthermore, irradiation treatment has been found to eliminate E. coli O157:H7, consequently the USDA has created regulations on irradiation of beef products to eliminate these pathogens (Vogt and Dippold, 2005).…”
Section: Pathogens Associated With Ground Beefmentioning
confidence: 99%
“…These guidelines outline a minimum time and temperature combination that must be met to achieve a 6.5-log reduction of Salmonella in beef products (Vasan et al, 2014). Salmonella causes an estimated one million cases of food born illness, which results in nearly 400 deaths a year (Scallan et al, 2011).…”
Section: Pathogens Associated With Ground Beefmentioning
confidence: 99%
“…The authors found significant differences in decimal reduction of E. coli among various strains at 55 °C. The time for Salmonella decimal reduction was found to be significantly less than O157 and non-O157 Shiga toxigenic E. coli (Vasan et al, 2014).…”
mentioning
confidence: 78%
“…The inactivation results of foodborne pathogens in ground beef by the energy of radio frequency indicated that the cooking of meatballs with the combination of radio frequency and convection cooking reduced the levels of E. coli O157:H7, Salmonella, and Listeria monocytogenes to the non-detectable levels in 5.5 minutes (Schlisselberg et al, 2013). It has also been reported that the efficacy of treatments with regards to pathogen inactivation changes with products and strains (Vasan, Geier, Ingham, & Ingham, 2014). The authors found significant differences in decimal reduction of E. coli among various strains at 55 °C.…”
mentioning
confidence: 99%